2011
DOI: 10.1158/1078-0432.ccr-10-2537
|View full text |Cite
|
Sign up to set email alerts
|

WEE1 Kinase Targeting Combined with DNA-Damaging Cancer Therapy Catalyzes Mitotic Catastrophe

Abstract: WEE1 kinase is a key molecule in maintaining G 2 -cell-cycle checkpoint arrest for premitotic DNA repair. Whereas normal cells repair damaged DNA during G 1 -arrest, cancer cells often have a deficient G 1 -arrest and largely depend on G 2 -arrest. The molecular switch for the G 2 -M transition is held by WEE1 and is pushed forward by CDC25. WEE1 is overexpressed in various cancer types, including glioblastoma and breast cancer. Preclinical studies with cancer cell lines and animal models showed decreased canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
196
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(204 citation statements)
references
References 79 publications
7
196
0
1
Order By: Relevance
“…Inhibition of Wee1 potentiates DNA-damaging chemotherapeutics and radiotherapy and has cytotoxic effects as a single agent (19)(20)(21)(22). The consensus view is that Wee1 inhibition facilitates tumor cell killing through G 2 /M checkpoint inactivation, which would catalyze mitotic catastrophe (23)(24)(25). As expected, Wee1 inhibition is synergistic with DNA-damaging agents, specifically in TP53-mutant cancer cell lines (3).…”
mentioning
confidence: 66%
“…Inhibition of Wee1 potentiates DNA-damaging chemotherapeutics and radiotherapy and has cytotoxic effects as a single agent (19)(20)(21)(22). The consensus view is that Wee1 inhibition facilitates tumor cell killing through G 2 /M checkpoint inactivation, which would catalyze mitotic catastrophe (23)(24)(25). As expected, Wee1 inhibition is synergistic with DNA-damaging agents, specifically in TP53-mutant cancer cell lines (3).…”
mentioning
confidence: 66%
“…Since the G2 phase of the cell cycle provides a pause during which post-replication errors and breaks are corrected, its premature termination by Wee1 inhibition might promote the mitotic death of cells failing to complete repair. 12,25,35 This could be particularly relevant to pancreatic cancers, given their high degree of genomic instability. However, there was no significant single agent activity in our PDX models, which is consistent with the low response rate of MK-1775 (AZD1775) in human clinical trials.…”
Section: Mk-1775 (Now Azd1775mentioning
confidence: 99%
“…Many of the functions of ATR are mediated through phosphorylation and activation of Chk1, and while Chk1 inhibitors have exhibited promising radiosensitising effects in preclinical studies, toxicity issues have hampered their clinical development. More recently, inhibition of Wee1, another kinase that promotes G2/M checkpoint activation in response to radiation, has emerged as a potential therapeutic strategy [17]. As with ATM inhibitors, a number of studies have indicated that the effects of ATR or Wee1 inhibitors are more pronounced in p53 defective contexts [18,19].…”
Section: Cell Cycle Checkpoint Inhibitorsmentioning
confidence: 99%